Sararo, Legazpi! a mutable recreational-cum-evacuation center for community resilience - Candano, Danielle Bea C.; Chua, Johannes Vincent F. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Natural disaster often hinder urban development, especially in small settlements that are highly exposed to calamities. The project proposes a mutable evacuation center in Legaspi City, Albay to serve as a recreational and civic center during regular use. The study focuses on how spatial resilience and community resilience can empower and protect vulnerable communities from natural disasters. Resilient design goes beyond the physical strength of our structures and includes how spaces relate to one another to form a cohesive system. Through architecture, we can improve our disaster risk mitigation practices and pave the way for a lasting development.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Mutable evacuation center -- Albay -- Philippines